Pengembangan Industri Kreatif dari Iluminasi Naskah Kuno Pariangan: Studi Motif Batik Pariagan, Sumatra Barat - Irwan Malin Basa (Masyarakat Pernaskahan Nusantara (The Indonesian Association for Nusantara Manuscripts, Manassa), 2019)
Abstract: This article discussess about the creative industry development from the illumination of manuscripts in Pariangan. This research was conducted in Pariangan for six months. A case study approach was applied in this research with some consideration. First, Pariangan is called as one of the most beautiful villages in the world since 2012. It was anounced by the most popular travel magazine in America named American Budget Travelers. Second, it has many traditional manuscripts written in Arabic, Malay and Minang language. The manuscripts were saved in surau, in traditional houses and also as a personal collection. Most of the the manuscripts have different beautiful illumination. Third, to empower local people to revitalize their “lost” tradition to make the design of batik. The result of this research shown that there were twenty five of the batik designs which performs local wisdom of Pariangan. Until now there were 13 of the designs have been registered to the ministry of Law and Human Right of the Republic of Indonesia. The last one is local people of Pariangan are able to make batik again. — Abstrak: Tulisan ini membahas masalah pengembangan industri kreatif dari iluminasi naskah kuno yang ada di Pariangan, Tanah Datar, Sumatera Barat. Penelitian ini menggunakan metode case study research dan dilaksanakan selama enam bulan. Ada beberapa alasan untuk melaksanakan penelitian ini di Pariangan. Pertama, Pariangan adalah desa terindah di dunia menurut majalah pariwisata terkenal dari Amerika yaitu American Budget Travelers. Kedua, Pariangan memiliki banyak naskah kuno yang memiliki ragam hias atau iluminasi yang indah dan naskah naskah tersebut masih tersimpan di surau, rumah gadang dan koleksi pribadi masyarakat. Ketiga, untuk memberdayakan penduduk lokal tentang tradisi mereka yang pernah hilang yaitu mencelup kain. Sebagai hasilnya, sudah tiga belas design batik yang didaftarkan sebagai Hak Cipta dan Hak Kekayaan Intelektual ke Kementerian Hukum dan Hak Azazi Manusia Republik Indonesia. Dan yang terakhir adalah masyarakat Pariangan bisa melestarikan tradisi mereka dengan membuat batik kembali yang dulu pernah hilang.